A self-powered battery-driven drug delivery device that can function as a micromotor and galvanically actuate localized payload release. (December 2019) - Cui, Qinghua; Le, Thanh-Ha; Lin, Yu-Jung; Miao, Yang-Bao; Sung, I-Ting; Tsai, Wei-Bor; Chan, Hao-Yu; Lin, Zong-Hong; Sung, Hsing-Wen
Abstract: Most drug delivery vehicles lack thrust that propels them to disease sites for payload delivery. Herein, a microrod comprising a zinc (Zn) core and a positively-charged poly(3, 4-ethylenedioxythiophene) (PEDOT + ) shell incorporating an anionic model drug, which form a "galvanic cell" in an electrolyte solution, is proposed as a battery-driven drug delivery device. Upon immersion of the proposed Zn-based batteries in a physiological environment, two sets of redox reactions that compete with each other in a manner determined by the local pH occur spontaneously. At low pH, the reduction of H + to H2 bubbles, which are essential to propel the Zn batteries as micromotors, prevails, while at higher pH, the reduction of PEDOT + to actuate galvanically payload release dominates. Observations in mice suggest that the self-powered Zn batteries may rapidly react and move in the gastric fluid after oral administration, considerably improving their penetration and retention in the mucus layer for localized drug release, similar to those directly injected into the subcutaneous tissue. None of the investigated tissues exhibits any significant inflammation or cell apoptosis, revealing that the developed Zn-based batteries have potential to serve as safe drug delivery devices. Graphical abstract: At low pH, the reduction of H + to H2 bubbles, propelling the Zn battery as a micromotor, prevails, while at higher pH, the reduction of its PEDOT + shell, actuating galvanically payload release, dominates. Image 1 Highlights: A battery-driven delivery device that can target intended sites and be actuated to trigger drug release is developed. The delivery device comprises an inner rod of Zn and an outer shell of PEDOT +  incorporating an anionic model drug, SRB − . The Zn core, the PEDOT + SRB − shell, and the physiological pH solution form a "galvanic cell". In the acidic gastric medium, the reduction of H + to H2  bubbles prevails, propelling the delivery device as a micromotor. At the neutral gastric mucus layer, the PEDOT +  reduction dominates, actuating the payload release galvanically.